2019
DOI: 10.1016/j.nicl.2019.101907
|View full text |Cite
|
Sign up to set email alerts
|

Mild traumatic brain injury: The effect of age at trauma onset on brain structure integrity

Abstract: Mounting evidence suggests that mild traumatic brain injuries (mTBI) have long-term effects that interact with the aging process to precipitate cognitive decline. This line of research predicts that early exposure to brain trauma is particularly detrimental to long-term brain integrity. However, a second line of research into the effects of age at trauma onset predict that older brains are more vulnerable to the effects of mTBI than younger brains. We sought to determine whether patients who sustain a mTBI ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
0
25
1
Order By: Relevance
“…Studies that examined adults in the general population who were exposed to remote mTBI typically found higher AD, RD, and MD (but not FA) in areas that included the fornix/stria terminalis, anterior corona radiata, superior longitudinal fascilus, cingulum angular bundle, the anterior aspect of the corpus callosum, and frontal white matter ( 35 , 49 , 61 ). These studies demonstrated white matter differences in adults with remote mTBI compared to healthy controls who were either the same age or younger.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that examined adults in the general population who were exposed to remote mTBI typically found higher AD, RD, and MD (but not FA) in areas that included the fornix/stria terminalis, anterior corona radiata, superior longitudinal fascilus, cingulum angular bundle, the anterior aspect of the corpus callosum, and frontal white matter ( 35 , 49 , 61 ). These studies demonstrated white matter differences in adults with remote mTBI compared to healthy controls who were either the same age or younger.…”
Section: Resultsmentioning
confidence: 99%
“…The imaging techniques used in these studies were also diverse. However, there was evidence of different levels of metabolites in several brain regions for athletes compared to controls which may be indicative of neuroinflammation ( 48 , 62 , 66 , 73 ) and white matter disruption in widespread areas ( 49 , 52 , 71 ). As per the above sections, methodological considerations (i.e., distinct study designs and methods for selecting brain regions and quantifying metabolites) limit the conclusions that can be drawn from these data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis of studies conducted from 1995 to 2012 found that TBI and mTBI events are substantial risk factors for AD (36). The BBB disruption at the onset of TBI is relatively short-lived; however, the subsequent events lead to structural degeneration in the brain causing long-lasting cognitive impairments (37). Disruption of the BBB has been observed to be a marker of mild cognitive impairment independently of the neurofibrillary tangles (NFTs), tau protein, and Aβ amyloid plaques, indicating that substantial breakdown of the BBB itself contributes to cognitive decline in addition to exacerbating other neurodegenerative processes in AD (38).…”
Section: Traumatic Brain Injurymentioning
confidence: 99%